Pluralisme dalam Perspektif Pemikiran Gus Dur dan Nurcholish Majid - Asripa Asripa; Devy Habibi Muhammad; Ari Susandi (FALASIFA : Jurnal Studi Keislaman, 2021)
The purpose of this research is to understand the thoughts of Gus Dur and Nurcholish Majid about pluralism. In Indonesian society, which is pluralistic, friction between understandings in various structures of community groups is unavoidable. For this reason, it is important to understand how Gus Dur and Nurcholish Majid think in terms of pluralism. And what are the similarities and differences in their thinking. This study uses a qualitative descriptive approach and the type of research is library research. Data collection comes from several books and scientific works in the form of journals that are relevant to the themes in the research. The data processing in this study was analyzed in accordance with a count approach (statistics) but through the presentation of thoughts, opinions of experts, or information related to the problem. Gus Dur's idea of ​​pluralism has the main goal of creating harmonization of a pluralistic Indonesian society. And according to Nurcholish majid pluralism is a positive value and grace from God to mankind to enrich the growth of diverse cultures. Tujuan dari penelitian ini adalah untuk memhami pemikiran Gus dur dan Nurcholish Majid tentang pluralisme. Dalam masyarakat indonesia yang mejemuk pergesekan antar paham diberbagai struktur kelompok masyarakat tidak dapat dihindari. Untuk itu penting memahami bagaimana pemikiran Gus Dur dan Nurcholish Majid dalam hal pluralisme. Serta apa saja persamaan dan perbedaan dalam pemikiran keduanya. Penelitian ini menggunakan metode pendekatan deskriptif kualitatif dan jenis penelitiannya adalah penelitian kepustakaan (library reseach). Pengumpulan data bersumber dari beberapa buku dan karya ilmiah berupa jurnal yang relevan dengan tema yang ada dalam penelitian. Adapun Pengolahan data dalam penelitian ini dianalisis sesuai dengan pendekatan hitungan (statistik) tetapi memalui penyajian pemikiran,pendapat para ahli, atau informasi yang berhubungan dengan permasalahan. Gasasan pluralisme Gus Dur memiliki tujuan utama yaitu menciptakan harmonisasi masyarakat Indonesia yang majemuk. Dan menurut Nurcholish majid pluralisme merupakan nilai positif dan rahmat dari Tuhan kepada umat manusia untuk memperkaya pertumbuhan budaya yang beraneka ragam.